DEVELOPMENT OF CATTLE CATTLE WITH MODIFICATION MODEL TO PREVENT BACTERIOLOGICAL CONTENT OF E. COLI CONTENT IN A WELL WAS DAILED IN GAMPONG LAMPASI ENGKING, DISTRICT DARUL IMARAH, ACEH BESAR DISTRICT - hamdani; Zubir (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
The presence of Colifaecal bacteria in clean water indicates contamination caused by dirt. The discovery of E. Coli in water is thought to pose a threat to human health because the water is suspected of containing pathogenic microorganisms, which include viruses, bacteria, protozoa, and parasites which are transmitted through fecal material. The study aimed to determine the relationship between the distance between cattle sheds and the quality of dug well water on the bacteriological content of E. Coli in Gampong Lampasi Engking, Darul Imarah District, Aceh Besar District in 2018. This research is a Quasi Experiment type of non-equivalent control group design. The subjects in this study were the effect of the number of E.coli after and before the modified cattle barn on the dug wells around the cowshed in Lampasi Engking Village, Darul Imarah District, Aceh Besar District with a total of 4 dug wells. The results showed that the number of E. coli before the cage was modified was 26 MPM while after the modification there was a decrease in the number of E.coli in dug wells of 7 MPM in Gampong Lampasi Engking, Darul Imarah District, Aceh Besar District. The conclusion is that there is a difference in the content of E.Coli in the wells that have not been modified in cow pens with the amount of E.Coli bacteria content after being modified where the value of p = 0.070. It is hoped that the Lecturer can add information material that can be used as a reference for the development of science or further research for those who need it, especially regarding models of Modification of cattle pens to reduce the bacteriological number of E. Coli in dug wells around cow pens.